STRATEGI MARKETING PUBLIC RELATIONS PT KEMUNING MULIA JAYA DALAM MEMPROMOSIKAN KLINIK GIGIKU SEHAT - Muntaha Meliala, Robbikal; Yulianah, Yuwarni (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Social Media nowadays become alternative media to run function of Marketing Public Relations. PT KemuningMulia Jaya has been participating in the service of teeth health care and mouth care used social media to promote its product brand of Klinik Gigiku Sehat. PT Kemuning Mulia Jaya has been established since 2010.This company was pioneered by Drg. Susan Widijaningsih with Deddy Andu Edgar Frederik as the owner of PT Kemuning Mulia Jaya. Marketing Public Relations of this company has created Promotion Program of March 2019 to attract customer attention. Data collection technique of this research consist of observation, interviews, study literature, and documentation. The analysis method that author used is qualitative descriptive approached. The result of the research has shown the use of social media by Klinik Gigiku Sehat effectively can communicate to the public became easier. The conclusion of the promotion programme for March 2019 consist of Voucher Promotion, and Dental Education through social media. To maintain a good relationship with public, Marketing Public Relations of Klinik Gigiku Sehat has worked periodically uploaded useful infographic to the public through social media. Strategy of Marketing Public Relations that they chose is Pull Strategy. Public Relations pattern that they applied to promote Klinik Gigiku Sehat only formula P for Publication, E for Event, I for Inform or Image and L for Lobbying.